2023
DOI: 10.1021/acsnano.3c00360
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-Free Nanodrug Based on Co-Assembly of Methylprednisolone Dimer and Rutin for Combined Treatment of Spinal Cord Injury

Abstract: Spinal cord injury (SCI), which is characterized by excessive inflammatory cell infiltration and accumulation of oxidative substance, would severely impede neurological functional recovery and lead to permanent and profound neurologic deficits and even disability. Methylprednisolone (MP) is the most commonly used clinical anti-inflammatory drug for SCI treatment, but high doses are typically required that can cause severe side effects. Here, we developed a carrier-free thioketal linked MP dimer@rutin nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Then PC12 or CTXTNA2 cells were pretreated with 200 or 400 μM H 2 O 2 before incubation with PFCN to establish the cellular oxidative stress model. 38 Specifically, when the oxidative stress damage was induced by 200 μM H 2 O 2 , a significant protection effect could be observed in the presence of >25 μg/mL PFCN and the relative cell viabilities were almost increased to 100% (Figure 2d). Similar results could be observed when cells were exposed to 400 μM H 2 O 2 (Figure 2e) or the incubation time was prolonged to 48 h (Figure S20).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Then PC12 or CTXTNA2 cells were pretreated with 200 or 400 μM H 2 O 2 before incubation with PFCN to establish the cellular oxidative stress model. 38 Specifically, when the oxidative stress damage was induced by 200 μM H 2 O 2 , a significant protection effect could be observed in the presence of >25 μg/mL PFCN and the relative cell viabilities were almost increased to 100% (Figure 2d). Similar results could be observed when cells were exposed to 400 μM H 2 O 2 (Figure 2e) or the incubation time was prolonged to 48 h (Figure S20).…”
Section: Resultsmentioning
confidence: 93%
“…Thus, the adjacent H 2 O 2 concentrations of 200 and 400 μM were chosen for the subsequent experiments. Then PC12 or CTXTNA2 cells were pretreated with 200 or 400 μM H 2 O 2 before incubation with PFCN to establish the cellular oxidative stress model . Specifically, when the oxidative stress damage was induced by 200 μM H 2 O 2 , a significant protection effect could be observed in the presence of >25 μg/mL PFCN and the relative cell viabilities were almost increased to 100% (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to being a hydrophobic modification moiety for enhancing drug loading, the addition of IDE within PKI NPs significantly improved the therapeutic effect of PTX prodrug-loaded NPs. IDE is the analogue of the endogenous antioxidant coenzyme Q10, which has been shown to alleviate inflammation and oxidative stress in brain disease, and to regulate inflammation and antioxidants after SCI can promote spinal cord repair . Hence, the positive therapeutic effect of IDE in SCI might be related to the mechanisms mentioned above.…”
Section: Pki Nps Inhibited Microglia Activationmentioning
confidence: 99%
“…Recently, great progress has also been made in activating endogenous neural stem cells (NSCs) to repair the structure and function of SCI in animal models via bioactive drugs, polymer scaffolds, and molecules. For example, in addition to its therapeutic effect on diabetes, metformin (Met) has been demonstrated to efficiently induce endogenous NSCs to proliferate and repair damaged structures in animal models of brain injury and stroke. In addition to supporting NSCs transplantation, polymer scaffolds can also support local release of bioactive molecules, induce endogenous NSCs proliferation and differentiation, and then enhance function repair. , More importantly, it was also found that the strategies to expand the limited regeneration by activating the proliferation of endogenous NSCs or transplanting exogenous stem cells are also affected by the harsh microenvironment at the injury sites, which could reduce stem cell survival and lead to the stem cells differentiating into astrocytes instead of neurons and oligodendrocytes. , Therefore, the integrated therapy strategy via improving the harsh microenvironment as well as promoting endogenous NSCs to repair the structure of SCI using robust biomaterials is considered to be one of the most promising therapeutic strategies for SCI repair. , Functional nanomaterials are an emerging and highly promising option for integrated therapy strategies, by combining different biologically active drugs into nanoparticles (NPs) or other nanoscale devices through covalent or noncovalent combinations . It is worth noting that for the central nervous system (CNS) injury diseases, including SCI, brain injury, and cerebral hemorrhage, due to the dysfunction of the integrity of the blood–brain/spinal barrier and the increase of vascular permeability, as well as the formation of excessive ROS and the acidic microenvironment at the injury site, nanoscale components have been confirmed to be significantly enriched at the injury site. In addition, in terms of drug delivery, functional nanomaterials also have the following advantages. First, nanomaterials could solve the problems of poor water solubility and prohibit the active molecules from fast clearance to prolong the action duration .…”
Section: Introductionmentioning
confidence: 99%
“…First, nanomaterials could solve the problems of poor water solubility and prohibit the active molecules from fast clearance to prolong the action duration . Second, nanomaterial-based targeted drug delivery usually achieves high concentration enrichment of drugs in designated areas, improves treatment effectiveness, and can solve potential side effects of drugs. , Third, they can simultaneously deliver multiple drugs and achieve synergistic effects of drugs with different biological properties. , …”
Section: Introductionmentioning
confidence: 99%